Association of obesity with physical activity, television viewing, video /computer gaming among school children in Mangalore - Kini, Sanjay; Ramasamy, Pavithra; Jaison, Merin; Raj, Reshma; RK, Ranjitha; Kundapur, Rashmi; Udaya Kiran, Nalam (Indian Journal of Community Health, 2015)
Introduction: There is an increasing prevalence of obesity worldwide in children which can be attributed to changes in lifestyle such as sedentary habits, television (TV) viewing, playing computer games, and consumption of snacks while watching television. The present study was done to find the association between obesity and TV viewing, computer game playing, sedentary lifestyle in children and also with a secondary objective to assess the association between blood pressure and TV/computer game viewing, sedentary lifestyle in children. Materials and methods: A cross sectional study was conducted at 4 high schools and Pre University Colleges (PUC’S) in and around Mangalore during the study period of 4 days from 6 -12 august 2014. 509 students were enrolled. Information was gathered by asking the subjects to fill up a structured questionnaire. Nutritional status was assessed based on Body mass index (BMI) and waist-hip ratio, waist-height ratio for all subjects. Blood pressure was measured for all the subjects. Results: It was found that among males 2.7% of students were obese and in females it was 2.3%. There was a significant association between blood pressure and consumption of snacks while watching TV and also between blood pressure and their habit of consumption / buying of snacks/ fast-food advertised in TV. A significant association was found between central obesity (Waist-hip ratio and Waist-height ratio) and the number of hours of physical activity per week in schools. Conclusion: There is a need to develop preventive intervention like reducing snack consumption while watching TV and increasing the time dedicated to physical activity.